EPISTEMOLOGI IRFANI (Sebuah Tinjauan Kajian Tafsir Sufistik) - Abshor, Muhammad Ulil (Jurnal At-Tibyan: Jurnal Ilmu Alquran dan Tafsir, 2018)
Irfani Epistemology is one of reasoning system known in Islamic knowledge tradition, besides these are Baya>ni and Burha>ni. It is different with of baya>ni and burha>ni based on holy scripture and logic. Irfani is based on kasyf (Illuminative), overflowing knowledge by presence without through reason analytic. The way of reaching is the exercise of soul (hearth) through the steps of certain sprituality (maqamat) and the experince of certain devine inspiration (hal). âIrfani Epistemology in study of tafsir known by the Tafsir of sufistik, this consists of two tipologies or variaty of interpretation is tafsir of Nazari sufistik and Isyari sufsistik. Both these tipologies are to be discussed in this research, the first tafsir interpretes the teks of holy Qurâan by a mistical theory and the second of that is using a number of qalb means (inner meaning) because the Tafsir of sufistik explores the aspect of inner meaning in teks or scripture. Historically, the development of sufistik exegesis had expanded since the second century of Hijriyah to the present. The Tafsir of sufistik is by means of validity couldnât be proved empirically, however the contex of sufistik (Irfan) is not based on external objection or logical sequence but it is by from itself, in fact the reality of self-consciousness in which is well-known in Sufistik (Inner experience) or Kasyf (Illuminative). Therefore it couldnât be examined based on correspondent or coherent validity. Further the object is not only immaterial and essential characteristic, but also it is swa-objective (self-object-knowledge), so what the matter is known as objective is a characteristic of analysis and appeared in the act of recognizing itself.